Accounting Treatment Of Interest Income On Capital Lease Services Based On Psak - Musyarrapa Musyarrapa; Andi Muhammad Nurul Afdhal; Andi Zulfayani (GENTARA: management and accounting research, 2025)
With unstable economic conditions, people are looking for quick and easy financing alternatives. PT Pegadaian (Persero) is present as a solution through capital lease-based pawn services. The main income from this activity comes from interest on capital lease services. As a state-owned enterprise, Pegadaian is required to prepare reliable financial statements in accordance with accounting standards. Therefore, it is important to examine how the accounting treatment of interest income is carried out, especially whether it is in accordance with the applicable PSAK. This study aims to determine the accounting treatment of interest income on capital lease services at PT Pegadaian (Persero). The aspects studied include recognition, measurement, presentation, and disclosure of interest income. The method used is descriptive qualitative, with data collection techniques in the form of interviews, observation, documentation, and literature study. This research began in January 2025 at the Watansoppeng Branch Pegadaian Office, South Sulawesi. The results showed that PT Pegadaian has applied accounting treatment in accordance with PSAK 71. Interest income is recognized on an accrual basis using the effective interest rate method, presented in the income statement, and disclosed in detail in the notes to the financial statements. This shows that the financial statements prepared have met the principles of transparency and relevance in accordance with applicable financial accounting standards